The socio-spatial context as a risk factor for hospitalization due to mental illness in the metropolitan areas of Portugal - Adriana Loureiro; Cláudia Costa; Ricardo Almendra; Ângela Freitas; Paula Santana (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract This study's aims are: (i) identifying spatial patterns for the risk of hospitalization due to mental illness and for the potential risk resulting from contextual factors with influence on mental health; and (ii) analyzing the spatial association between risk of hospitalization due to mental illness and potential risk resulting from contextual factors in the metropolitan areas of Lisbon and Porto, Portugal. A cross-sectional ecological study was conducted by applying statistical methods for assessing spatial dependency and heterogeneity. Results reveal a spatial association between risk of hospitalization due to mental illness and potential risk resulting from contextual factors with a statistical relevance of moderate intensity. 20% of the population under study lives in areas with a simultaneously high potential risk resulting from contextual factors and risk of hospitalization due to mental illness. Porto Metropolitan Area show the highest percentage of population living in parishes with a significantly high risk of hospitalization due to mental health, which puts forward the need for interventions on territory-adjusted contextual factors influencing mental health.